(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This study is set to assess the practice and challenges faced by TESL students at a local teacher training institute during their first practicum practices at selected Malaysian primary schools. This research is of significant value, as the 17 student- teachers’ experiences need to be made known; the findings on the transitional move from a safe protected college environment into the unknown territory of school surroundings. Each of these trainee-teachers had leapt into the role of a teacher in the 21st century language class. They would each maintain daily and weekly reflective journals throughout their practicum period to document their teaching concerns and the level of confidence they put into their abilities to teach and manage their primary school students. These findings from the questionnaires were reported. The data obtained from the study participants were analyzed qualitatively. The results of the study reveal that:- i) student-teachers have positive perception towards the role of practicum program in promoting their pedagogical skills as well as subject matter knowledge; ii) school mentors failed in providing the necessary support for practicum student-teachers. This research enables to shed more light into the areas of second language teaching in the classroom as the findings would be able to provide more support for future management and development of teacher education. Furthermore, these student-teachers could understand themselves better throughout the month extended practicum. The ability to self-monitor and self-appraise themselves are valuable skills to be acquired by these student-teachers for their personal and autonomous and continuous self-assessments to become effective second language teachers.